Computer aided design and drafting used in architecture and interior design, does its benefits justify its high cost? - Sarmiento, Lara Kristine D.; Florendo, Raquel Baltazar (1991.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Architectural design -- Data processing -- Economic aspects; Computer-aided design -- Economic aspects